Application of Social Media Threads in College Libraries - Saputra, Ricco Herdiyan; Waziana, Winia (Jurnal El-Pustaka, 2023)
The development of information technology has brought significant changes in various sectors, including university libraries. Social media, as one of the information technology innovations, has become an effective tool in expanding access and improving library services. This research focuses on the application of social media "threads" as a strategy to increase the effectiveness of college libraries in providing services and connecting with users.This research uses a qualitative approach with case studies of several university libraries that have actively implemented social media "threads". Data was collected through interviews with library staff, observation of user behavior, and analysis of social media content. The research results show that the application of social media "threads" has provided real benefits in increasing access to information, facilitating communication between libraries and users, and promoting library services effectively.Additionally, this research also identified challenges faced in implementing social media "threads," including time management, expanding the user base, and the need for library staff training. The results of this research provide valuable insight for university libraries in developing strategies for utilizing social media "threads" to improve services and interactions with users.